Theoretical Substantiation of the Formation of the Language Competence of Students in the Course of Studying Syntactic Norms - Shaymanova Yulduz Toshniyazovna; Eshniyazova Maysara Beknazarovna (Periodica Journal, 2023)
The practical significance of the article lies in the focus of its results on improving the preparation of students in the Uzbek language: in determining additional opportunities for students to master a certain set of learning activities aimed at developing their competency-based skills, involving the use of acquired knowledge in various situations of solving language problems. The developed methodology for the formation of the language competence of students makes it possible to train students on an activity basis.
Keywords: unified process; assimilation; knowledge